Colloidal Gold Immunochromatographic Strip Assay for the Detection of Azaperone in Pork and Pork Liver - Lin, Lu (ACS Omega, 2020)
[Image: see text] In this study, a highly sensitive and specific monoclonal antibody (mAb) against azaperone was produced. The mAb belonged to the IgG2b subtype and its half maximal inhibitory concentration (IC(50)) was 0.46 ng/mL. The limit of detection value was 0.081 ng/mL and the linear range (IC(20)–IC(80)) was 0.165–1.29 ng/mL. Based on this anti-azaperone mAb, a colloidal gold immunochromatographic strip assay method was established for the detection of azaperone in pork and pork liver samples. For pork samples, the cutoff value of the colloidal gold immunochromatographic strip assay was 10 ng/g, and the cutoff value was also 10 ng/g in pig liver samples. This colloidal gold immunochromatographic strip assay is a rapid, simple, and practical method for the detection of azaperone in pork and pork liver samples available in markets.